Hemophagocytic Lymphohistiocytosis Associated with Salmonella typhi Infection in a Child: A Case Report with Review of Literature - Juanita Uribe-Londono; Lina Maria Castano-Jaramillo; Laura Penagos-Tascon; Andrea Restrepo-Gouzy; Andres-Felipe Escobar-Gonzalez (Case Reports in Pediatrics)
We present the case of an 8-year-old girl with hemophagocytic lymphohistiocytosis secondary to a Salmonella typhi infection. She received antibiotic treatment and intravenous immunoglobulin with complete resolution of the symptoms. We present a review of previously reported pediatric cases and propose a gradual approach to treatment.